The technical efficiency of chrysanthemum flower farming: A stochastic frontier analysis - Khoiriyah, Nikmatul; Susilowati, Dwi; Mintyastuti, Dyah Sri; Ali, Roihan Muhammad; Forgenie, David (Anjoro: International Journal of Agriculture and Business, 2023)
Over the years, improvements in standard of living and well-being have resulted in an increase in the demand for chrysanthemums, however, the recent COVID-19 pandemic has resulted in a fall in demand. As a result, this study investigates the technical efficiency of chrysanthemum farming and its major determinants. The study was conducted in Bumiaji Village, Bumiaji District, Batu, East Java, Indonesia between January and September 2022. Data was collected via interviews with chrysanthemum farmers using a questionnaire. A total of 35 chrysanthemum farms were selected using random sampling technique. The data was then analyzed using the stochastic frontier method combined with Maximum Likelihood Estimation (MLE). The results reveal that the efficiency of chrysanthemum farming is dominated by 0.91 to 0.93. (65.71 percent). Since technical efficiency is close to one, most chrysanthemum farmers are close to achieving maximum efficiency. The technical efficiency of chrysanthemum blooms was influenced by land area, inorganic fertilizers, organic fertilizers, and pesticides, but not by seeds or labor. The land area negatively impacts technical efficiency, implying that increasing land size decreases technological efficacy of chrysanthemum farming. Inorganic fertilizers, organic fertilizers, and pharmaceuticals have a positive effect or contribute to an increase in inorganic fertilizers, organic fertilizers, and pesticides. In terms of technical efficacy, chrysanthemum cultivation is close to its zenith. It is not necessary to exert effort to reach this ideal land, but inorganic fertilizers, organic fertilizers, and pesticides can assist.